Case studies to illustrate data wrangling approaches and share R scripts - CGIAR Platform for Big Data in Agriculture (2019)
These case studies are stable and widely available for uptake, and have been used in training workshops covering data processing and analysis using R, organized under Module 1 of the Big Data Platform.